“Diagnóstico de la existencia y uso de la maquinaria agrícola en el cantón Babahoyo, provincia de los Ríos Ecuador” - Ramírez Mayorga, Stalin Alfonso (2023)
In this study, the survey methodology will be applied to a probabilistic sample of 180 farmers obtained through the calculation of a simple random sampling. To obtain all the information in the parishes where it is proposed to evaluate the existence and use of agricultural machinery in the Babahoyo canton, province of Los Ríos Ecuador only in agricultural areas of short cycle crops, the main objective of this investigative work is to analyze the availability of agricultural machinery in the canton, establishing the area of short cycle land, classifying agricultural machinery and characterizing the use of agricultural machinery in short cycle crops in the Babahoyo canton, province of Los Ríos Ecuador. The purpose of using agricultural machinery in short cycle crops is to have greater production, facilitate soil preparation and crop management in the Babahoyo canton. This study will carefully detail the use and existence of agricultural machinery in the different parishes of the Babahoyo canton, emphasizing and referring to the important role they play in short-cycle crops. The tractors most used by those surveyed in the Babahoyo area and its surrounding parishes were the 90 hp ones with 23.33% and the 120 hp ones with 17.78%. Regarding the combines, the most used power was the 105 hp with 39.44% followed by 95 hp with 17.78% and the most used fumigator was the 600 liter capacity with 75%.